Vomiting in the pediatric age group. Issue 5 (October 2009) - Mullen, Neil
Vomiting is a common complaint in any healthcare facility that deals with children. A child recently presented to our emergency department with an occult cause of vomiting, which led to the development of the following differential diagnosis of vomiting in children. Although usually of gastrointestinal origin, vomiting can be caused by the dysfunction of many different organ systems, the results of which may range from benign to life threatening. The differential diagnosis is presented in order of frequency, in order to make it as clinically relevant as possible, and then each section is further broken down to the pathophysiology, the historical facts, the pertinent physical examination findings, and the therapeutics of each diagnosis is discussed in variable detail.